Characterization of Porang and Xanthan Gum Solutions for Polymer Flooding - Sutiadi, Andrian; Siahaya, Jacob; Maulida, Fajri; Mardiana, Dwi Atty; Fathaddin, Muhammad Taufiq; Setiati, Rini; Rakhmanto, Pri Agung; Irawan, Sonny (Journal of Earth Energy Engineering, 2024)
Porang tubers contain glucomannan which is used in various industries. Porang is a biopolymer that has the potential to be applied in polymer flooding in oil reservoirs. In this research, a combination of porang and Xanthan gum was used for displacing oil in the laboratory. The samples analyzed varied with polymer concentrations of 2000, 4000, and 6000 ppm respectively for porang solution, Xanthan gum, and a mixture of porang and Xanthan gum. The salinity of the formation water used in this research was 6000, 12000 and 18000 ppm. The experiment aimed to observe the characteristics and performance of porang and Xanthan gum including testing for compatibility, viscosity, adsorption and sandpack flooding. Based on the test results, all samples were compatible. The application of a mixture of porang and Xanthan gum provided lower adsorption compared to the application of only Xanthan gum. The highest reduction in adsorption value given was 3.545 mg/gr. The highest viscosity and additional recovery factor were given by a mixture of porang and Xanthan gum with a concentration of 6,000 ppm and a salinity of 18,000 ppm, namely 284.72 cP and 16.1%, respectively.